2015
DOI: 10.1089/neu.2014.3810
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Past Concussions Are Associated with Ongoing Post-Concussive Symptoms but Not Cognitive Impairment in Active-Duty Army Soldiers

Abstract: The extent to which multiple past concussions are associated with lingering symptoms or mental health problems in military service members is not well understood. The purpose of this study was to examine the association between lifetime concussion history, cognitive functioning, general health, and psychological health in a large sample of fit-for-duty U.S. Army soldiers preparing for deployment. Data on 458 active-duty soldiers were collected and analyzed. A computerized cognitive screening battery (CNS-Vital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
3
31
2
Order By: Relevance
“…Our health symptom findings coincide with Miller and colleagues [ 27 ] research, which demonstrated that active duty Soldiers with two or more head injuries (<3 months) reported more health symptoms. Alternatively, work from Dretsch and colleagues [ 28 ] in active duty Soldiers preparing for deployment found an association between three or more concussions and increased rates of post-concussive symptoms measured by the neurobehavioral symptom inventory, which coincides with our CMI and Kansas GWI criteria findings. However, Miller et al [ 27 ] only grouped Soldiers by no, one, or two or more mTBIs.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our health symptom findings coincide with Miller and colleagues [ 27 ] research, which demonstrated that active duty Soldiers with two or more head injuries (<3 months) reported more health symptoms. Alternatively, work from Dretsch and colleagues [ 28 ] in active duty Soldiers preparing for deployment found an association between three or more concussions and increased rates of post-concussive symptoms measured by the neurobehavioral symptom inventory, which coincides with our CMI and Kansas GWI criteria findings. However, Miller et al [ 27 ] only grouped Soldiers by no, one, or two or more mTBIs.…”
Section: Discussionsupporting
confidence: 85%
“…However, Miller et al [ 27 ] only grouped Soldiers by no, one, or two or more mTBIs. Therefore, it is possible that the Soldiers with three or more mTBIs were driving the higher rate of symptom endorsement, which would be more consistent with the work of Dretsch [ 28 ].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…2 Indeed, a subset of individuals can experience persistent physical, cognitive, and emotional post-concussive symptoms (PCS) after single or multiple TBI. 3,4 Numerous epidemiological studies have investigated prognostic factors and adverse consequences of persistent PCS. [5][6][7][8] Although there is still open discussion regarding the specificity of PCS consequent to TBI, 4,9 TBI and persistent PCS are associated with short-term sequelae, including emotional distress, difficulty in making a return to society, inability to return to work, and reduced quality of life, 10 and long-term events, including increased risk of Alzheimer's disease, Parkinson's disease, mild cognitive impairment, depression, and bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies find that deployment‐related TBI is significantly associated with postconcussive symptoms, distress, and decreased health‐related quality of life (Brickell, Lange, & French, ; Dretsch, Silverberg, & Iverson, ; Vanderploeg et al., ), critical and meta‐analytic reviews of the literature (Broshek, De Marco, & Freeman, ; Panayioutou, Jackson, & Crowe, ) and longitudinal studies of predeployment characteristics (Lee, Garber, & Zamorski, ) indicate that a variety of psychological and contextual factors (e.g., litigation) account for much of the variance associated with chronic emotional and psychosocial problems reported post‐TBI. Consequently, research is needed to isolate the psychological characteristics associated with complicated adjustment among Veterans with deployment‐related TBI, preferably with variables that can inform assessment practices and psychological interventions.…”
mentioning
confidence: 99%